Characteristics of Attempted Suicide by Patients with Schizophrenia Compared with Those with Mood Disorders: A Case-Controlled Study in Northern Japan - Ishii, Takao; Hashimoto, Eri; Ukai, Wataru; Kakutani, Yohei; Sasaki, Ryuji; Saito, Toshikazu (PLOS ONE, 2014)
Recent reports suggest a lifetime suicide risk for schizophrenia patients of approximately 5%. This figure is significantly higher than the general population suicide risk consequently, detection of those at risk is clinically important. This study was undertaken to define the characteristics of suicide attempts by schizophrenia patients compared with attempts by patients with mood disorders. All patients were diagnosed using the ICD-10 criteria. The study population comprised 65 patients with F2 disorders (schizophrenia, schizotypal and delusional disorders), i.e., “the F2 group”, and 94 patients with F3 disorders (mood disorders), i.e., “the F3 group”, who presented in the clinical setting of consultation-liaison psychiatry. The F2 group had a significantly younger mean age and significantly higher ratios of ‘past/present psychiatric treatment’ and ‘more than 3 months interruption of psychiatric treatment’. In contrast, the ratios of ‘physical disorder comorbidity’, ‘alcohol intake at suicide attempt’ and ‘suicide note left behind’ were significantly higher in the F3 group. The F2 group attempted suicide by significantly more serious methods. Furthermore, ‘hallucination-delusion’ was the most prevalent motive in the F2 group and was the only factor that showed a significant association with the seriousness of the method of suicide attempt (OR = 3.36, 95% CI: 1.05–11.33).